Immuno and Affinity Cytochemical Analysis of Cell Wall Composition in the Moss Physcomitrella patens - Berry, Elizabeth A.; Tran, Mai L.; Dimos, Christos S.; Budziszek, Michael J.; Scavuzzo-Duggan, Tess R.; Roberts, Alison W. (Frontiers in Plant Science, 2016)
In contrast to homeohydric vascular plants, mosses employ a poikilohydric strategy for surviving in the dry aerial environment. A detailed understanding of the structure, composition, and development of moss cell walls can contribute to our understanding of not only the evolution of overall cell wall complexity, but also the differences that have evolved in response to selection for different survival strategies. The model moss species Physcomitrella patens has a predominantly haploid lifecycle consisting of protonemal filaments that regenerate from protoplasts and enlarge by tip growth, and leafy gametophores composed of cells that enlarge by diffuse growth and differentiate into several different types. Advantages for genetic studies include methods for efficient targeted gene modification and extensive genomic resources. Immuno and affinity cytochemical labeling were used to examine the distribution of polysaccharides and proteins in regenerated protoplasts, protonemal filaments, rhizoids, and sectioned gametophores of P. patens. The cell wall composition of regenerated protoplasts was also characterized by flow cytometry. Crystalline cellulose was abundant in the cell walls of regenerating protoplasts and protonemal cells that developed on media of high osmolarity, whereas homogalacturonan was detected in the walls of protonemal cells that developed on low osmolarity media and not in regenerating protoplasts. Mannan was the major hemicellulose detected in all tissues tested. Arabinogalactan proteins were detected in different cell types by different probes, consistent with structural heterogeneity. The results reveal developmental and cell type specific differences in cell wall composition and provide a basis for analyzing cell wall phenotypes in knockout mutants.